2021
DOI: 10.1093/treephys/tpaa175
|View full text |Cite
|
Sign up to set email alerts
|

Drought elicits contrasting responses on the autumn dynamics of wood formation in late successional deciduous tree species

Abstract: Research on wood phenology has mainly focused on reactivation of the cambium in spring. In this study we investigated if summer drought advances cessation of wood formation and if it has any influence on wood structure in late successional forest trees of the temperate zone. The end of xylogenesis was monitored between August and November in stands of European beech and pedunculate oak in Belgium for two consecutive years, 2017 and 2018, with the latter year having experienced an exceptional sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…At the same site of our sampling, Dox et al (2021) found that the end of wood formation in oak occurs earlier under drought conditions while this parameter is rather insensitive to drought in beech. In 2019, the authors found that wood formation in oak stopped earlier (DOY = 262) than in 2018 (DOY = 282 in Dox et al, 2021). As the drought in 2019 was even more pronounced than in 2018 (see above), the results corroborate the drought sensitivity of wood formation in oak.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…At the same site of our sampling, Dox et al (2021) found that the end of wood formation in oak occurs earlier under drought conditions while this parameter is rather insensitive to drought in beech. In 2019, the authors found that wood formation in oak stopped earlier (DOY = 262) than in 2018 (DOY = 282 in Dox et al, 2021). As the drought in 2019 was even more pronounced than in 2018 (see above), the results corroborate the drought sensitivity of wood formation in oak.…”
Section: Discussionmentioning
confidence: 63%
“…Xylogenesis can be divided into five sequential processes: (1) cell division and (2) cell enlargement, which drive the growth in size; (3) cell-wall thickening and (4) cellwall lignification, which are mainly responsible for the increase in mass and C sequestration (Cuny et al, 2015); and (5) programmed cell death, which allows the woody cell skeleton to be used as mechanical support and conduit for water transport. The wood formation and its dynamics are strongly influenced by environmental conditions, such as the temperature, day length, and water availability (Delpierre et al, 2016;Dox et al, 2021). Therefore, climate change is expected to affect the tree growth and carbon accumulation through the modulation of the timing and duration of xylogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…and four birches (Betula pendula Roth) in the KS and four beeches and four oaks (Quercus robur L.) in the PB. The trees were chosen because their aboveground wood and leaf phenology have been extensively monitored since 2017 in the framework of the LEAF-FALL project [68][69][70][71][72][73]. As such, concurrent measurements allowed the integration of results on both the belowand aboveground phenology in deciduous trees.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…Therefore, we currently lack a mechanistic explanation of frequently observed individual growth responses to adverse climatic conditions which may ultimately result in neighboring dying and surviving trees of the same species (Cailleret et al, 2017 ). Even though first assessments have identified soil properties, stand structure, and micro-climate as influencing factors of forest decline and tree mortality (Lévesque et al, 2013 ; Rehschuh et al, 2017 ; Buras et al, 2018 ), the eco-physiological processes that govern the fate of single trees still need further investigation (Bascietto et al, 2018 ; D'Andrea et al, 2019 ; Dox et al, 2020 , 2021 ; Schuldt et al, 2020 ). One reason for this important research gap is related to the fact that key eco-physiological processes such as sap flow, regulation of leaf water potential, and changes in xylem conductivity cannot be studied retrospectively for dead trees.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the value of the aforementioned retrospective investigations, a deeper process-based understanding of forest decline can only be achieved by intensively monitoring stressed and/or dying trees throughout the stress period and the process of death (Bascietto et al, 2018 ; D'Andrea et al, 2019 ; Dox et al, 2020 , 2021 ; Scharnweber et al, 2020 ; Schuldt et al, 2020 ). As mentioned above, this however requires timely installation of monitoring equipment.…”
Section: Introductionmentioning
confidence: 99%